Likuiditas Saham Dan Kebijakan Dividen: Bukti Dari Lingkungan Yang Menganut Sistem Pajak Tradisional - Alexander Natanael Silaban; Hersugondo Hersugondo (JEMAP, 2021)
This research has the purpose to identify whether stock liquidity has a correlation with dividend policy on companies that listed in Indonesia stock exchange from 2017 until 2019. After controlling endogenous factor that determining dividend policy, Findings shows that stock liquidity doesn’t have a correlation to dividend policy because Indonesia has conventional tax system. Furthermore, writer finds that profitability and company leverage affect positively dividend policy.